The Math Kangaroo Competition - Akveld, Meike; Cáceres Duque, Luis; Nieto Said, José Heber; Sánchez Lamoneda, Rafael (Universidad Antonio Nariño, 2023)
In this paper we brie y explain what Math Kangaroo is. This is followed by a representative sample of Kangaroo questions, varying over all ages and all areas of mathematics that are covered by this competition. The paper concludes with the analysis of some statistical data and suggestions about how Math Kangaroo and this type of questions may be used in Math Clubs.